2014
DOI: 10.1002/ange.201402518
|View full text |Cite
|
Sign up to set email alerts
|

Iridium‐Catalyzed Enantioselective CH Alkylation of Ferrocenes with Alkenes Using Chiral Diene Ligands

Abstract: The first catalytic and enantioselective C À H alkylation of ferrocene derivatives with various alkenes was achieved. A cationic iridium complex, having a chiral diene ligand, and an isoquinolyl moiety as a directing group are essential for regioselective and enantioselective CÀH bond activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…Compared with the achievements attained via Pd-catalyzed enantioselective C-H bond functionalization, studies on iridium-or rhodium-catalyzed systems have progressed slowly, especially for the synthesis of planar chiral compounds. In 2014, the Shibata group developed the first Ir-catalyzed asymmetric C-H alkylation of ferrocenes with alkenes employing a chiral diene ligand, using an isoquinolin-2-yl directing group to suppress the secondary alkylation reaction (Figure 4A) [83]. On the basis of preliminary mechanistic studies, the catalytic cycle was proposed, as shown in Figure 4A.…”
Section: Ir/rh-catalyzed Asymmetric C-h Bond Functionalization Of Ferrocenesmentioning
confidence: 99%
“…Compared with the achievements attained via Pd-catalyzed enantioselective C-H bond functionalization, studies on iridium-or rhodium-catalyzed systems have progressed slowly, especially for the synthesis of planar chiral compounds. In 2014, the Shibata group developed the first Ir-catalyzed asymmetric C-H alkylation of ferrocenes with alkenes employing a chiral diene ligand, using an isoquinolin-2-yl directing group to suppress the secondary alkylation reaction (Figure 4A) [83]. On the basis of preliminary mechanistic studies, the catalytic cycle was proposed, as shown in Figure 4A.…”
Section: Ir/rh-catalyzed Asymmetric C-h Bond Functionalization Of Ferrocenesmentioning
confidence: 99%
“…Chemical shifts (δ) are reported in parts per million (ppm) referenced to residual solvent signals as internal standards. 19 F NMR spectra were referenced to benzotrifluoride as external standard. IR spectra were measured with a Perkin-Elmer FT 1710 spectrometer; intensities are indicated as br (broad), s (strong), m (medium), and w (weak).…”
Section: ■ Conclusionmentioning
confidence: 99%
“…10−13 For a greater part of the reported catalytic enantioselective C−H functionalizations of ODGsubstituted ferrocenes, Pd(OAc) 2 -catalyzed C(sp 2 )-C(sp 2 ) bond-forming reactions were presented, for instance, the highly enantioselective intramolecular ortho-alkenylation reported by You et al 14 A different interesting approach was the enantioselective intramolecular ortho-silylation and -germylation without the need of any particular ODG. 15−18 In addition to palladium, other noble metals were used as metal catalysts (Ir, 19 Rh, 20,21 Au, 22 Pt, 23 Cu 24 ). Therefore, the development of enantioselective C−H functionalization reactions of ferrocenes using economically as well as environmentally more benign metal catalysts is desirable.…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, Shibata and Shizuno reported the first iridium-catalyzed enantioselective CÀHa lkylation of ferrocenes with alkenes by using ac hiral diene as the ligand (Scheme 5). [15] The utilization of an appropriate directing group and choice of suitable diene ligand are key to the success of the reaction. The mono CÀHa lkylationp roduct was obtained as the dominant product with isoquinolineo r3 -methylpyridine as the directing group.…”
Section: Iridium-catalyzed Enantioselectivef Errocene Càhactivationmentioning
confidence: 99%